Analysis of factors of students’ stress of the English Language Department - Siwi Karmadi Kurniasih; Nur Hidayanto Pancoro Setyo Putro; Sudiyono Sudiyono (REID (Research and Evaluation in Education), 2020)
The study is aimed at further describing psychological factors inducing academic stresses of the students of the English Education Department, Yogyakarta State University (EED-YSU). The study is a continuation of a previous study that identifies sources of academic stress of students of EED-YSU. Data collection is conducted by an on-line survey technique. Confirmatory factor analysis is used for the data analyses. The results show six factors that become sources of students’ academic stresses, namely academic demands, parent-child relationship, traumatic experiences during childhood, peer pressures, financial matters, and self-expectancy. It is expected that other studies involving other factors of students’ academic stress be conducted to give further information on the topic.